Myles Brand’s College Sports Sustainability: “Amateurism”, Finances, and Institutional Balance - Fort, Rodney (Journal of Intercollegiate Sport, 2021)
As NCAA President, Myles Brand championed three major college sports initiatives: academic integrity, diversity, and sustainability. This paper is about the last. The first step is to distill the elements of college sports that Brand identified repeatedly in his documents and speeches on sustainability. The central elements are the NCAA definition of “amateurism”, athletic department finances, and balance between athletic and academic spending as a part of the university mission. An assessment of these three suggests that NCAA amateurism has changed since his death, in ways Brand stated should raise worries about sustainability. Finances and balance within the university have changed very little over the past ten years and appear sustainable into the future.